FAKTOR YANG MEMPENGARUHI HARGA SAHAM PERUSAHAAN MINING - JHON FILIFS B.N HUTAPEA; Satriyo Wibowo (E-Jurnal Manajemen Trisakti School of Management (TSM), 2021)
This research has the purpose to evaluate and analyze the effect of stock prices in mining companies. The factors tested are ROA, ROE, Company Size, PER, PBV, CR and DER and Stock Price. The research sample used is mining companies listed on the IDX for the period 2012-2019. The sampling technique used is purposive sampling to obtain 13 mining companies that meet the criteria in this study. The analysis method of this research uses multiple regression analysis.. The results showed that Price Book Value had a positive effect on stock prices. This is because investors have confidence in the prospect of mining companies in the future so that the demand for shares in this sector increases, as a result stock prices increase. The ROA, ROE, firm size, PER, CR, DER have no effect on stock prices.